The Legal Status of Paid Parking in Churches in the Perspective of Regional Taxes and Levies - Ferdinandus Ngau Lobo; Markus Hallan; Martinus Julianto Dae Djono; Rosalia Martha Jawa Kelen (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2025)
Introduction: Churches, as religious institutions, are generally exempt from taxation. However, the emergence of paid parking practices within church premises has not received public criticism. The public tends to view it as a form of voluntary participation rather than a commercial activity. This raises legal questions from the perspective of tax law and regional levies. Purposes of the Research: To examine the legal standing of paid parking practices at churches from the perspective of tax and regional levies. Methods of the Research: This study uses normative legal research with a statute approach, focusing on the analysis of legal materials through a literature review of laws and regulations as well as relevant legal literature. Results Main Findings of the Research: Paid parking within church premises is juridically categorized as a parking tax object, not a regional levy. However, referring to Article 77 paragraph (3) letter b of Law Number 28 of 2009, places of worship are exempt from tax if used solely for public services and not for commercial purposes. Since the parking proceeds are used to support church services, such practices should be excluded from the parking tax object. This indicates the need to expand the scope of tax exemption provisions to accommodate the essential function of places of worship.